The experimental testing of efficiency of forming methodology in chinese writing competence for future philologists (frontier level) - Asadchykh, Oksana; Savcheno, Alla (ScienceRise: Pedagogical Education, 2019)
Last years relations between Ukraine and the People’s Republic of China in many areas of life began to develop very quickly, which requires a large number of qualified Chinese language specialists, who could be realized in various areas of communication. The study describes the nature of the characteristics of testing the effectiveness of the formation of the competence in Chinese writing for future philologists at the frontier level of study, as well as justifies and confirms the choice of research hypothesis. Criteria and standards for assessing the competence in Chinese writing for future philologists are indicated. For a successful experiment, a significant number of scientific papers was processed, criteria for evaluating the information, necessary to determine the level of ability to write different types and subtypes of abstracts and written communications were suggested. Methods and materials, plan and structures, as well as the duration of the experiment are described. The important point is that the publication discusses the conditions, under which the effectiveness of the methodology for the formation of the competence (as a whole) in Chinese writing for future students (level B1) will be high. Along with this, examples of tasks and the ultimate goal of their implementation were brought. The article demonstrates the organizational and substantive aspects of the experimental teaching of students. Pre-experimental and post-experimental sections were carried out, the corresponding results of the effectiveness of the established methods of teaching Chinese writing were set forth. For a clearer perception, the results of the cuts were tabulated. An important point of the study is that, together with the demonstration of sections, the ratio of the level of student learning was illustrated